Ensino informal: proposta de utilização do enfoque CTS na abordagem das atividades experimentais utilizadas no show de energia - Barboza, Yago Patrick Calixto Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Considering the importance of working with the Science-Technology-Society approach in basic education, the possibility that this approach is addressed in an informal science teaching project entitled “Energy Show” is considered. The objective of this project is to work with experimental demonstration activities associated with the discipline of physics in a playful way, with students from public schools in the city and region. However, during the presentations of this project social and environmental issues are not discussed. Therefore, in this work, it is proposed to reformulate some of the experiments developed in this project in order to promote discussions by articulating the knowledge addressed with the technological and social aspects, in the context of an informal teaching activity. This way of approaching the experiments allows situations that involve society to be presented and that most people do not perceive, or ignore, such as, for example, the environmental and social risks that technological advances can cause, as well as helping the student. basic education to have a more critical view of the applications of science.

Considerando a importância de se trabalhar o enfoque Ciência-Tecnologia-Sociedade no ensino básico, considera-se a possibilidade de que esse enfoque seja abordado em um projeto de ensino informal de ciências intitulado “Show de Energia”. O objetivo desse projeto é o de trabalhar com atividades experimentais de demonstração associadas à disciplina de física de forma lúdica, com alunos de escolas públicas da cidade e região. No entanto, durante as apresentações desse projeto, as questões sociais e ambientais, não são discutidas. Sendo assim, neste trabalho, propõe-se uma reformulação de alguns dos experimentos desenvolvidos nesse projeto com o intuito de se promover discussões articulando-se os conhecimentos abordados com os aspectos tecnológicos e sociais, no contexto de uma atividade de ensino informal. Essa forma de abordar os experimentos propicia que sejam apresentadas situações que envolvem a sociedade e que a maioria das pessoas não percebe, ou ignora, como, por exemplo, os riscos ambientais e sociais que os avanços tecnológicos podem ocasionar, bem como pode auxiliar o aluno do ensino básico a ter uma visão mais crítica acerca das aplicações da ciência.
Informal education: proposal to use the STS approach in the approach to activities experimental used in the energy show
Keywords: Informal education; Energy show; CTS approach; Ensino informal; Show de energia; Enfoque CTS; Ensino – meios auxiliares; Física – Estudo e ensino; Tecnologia educacional